Blood chemistry of West African dwarf goats fed treated maize cob- and maize husk-based diets with mixture of microorganisms - Ibhaze, Gladys Abiemwense (2023)
The results showed that the dietary treatments significantly (P < 0.05) influenced the erythrocyte sedimentation rate which ranged from 0.50 to 1.00 mm/hr. Significant (P < 0.05) differences were observed in the globulin (28.16 g/dl diet A—59.26 g/dl diet B), aspartate aminotransferase (48.00 u/l diet E—128. 25 u/l diet C) and alanine aminotransferase (8.20 u/l diet A—33.33 u/l diet D). Serum electrolytes values were significantly (P < 0.05) influenced by dietary treatments.